Measuring Perceived e-Services Quality on Satisfaction of Islamic Saving and Credit Cooperatives - Ningsih, Ekawati Rahayu; Haryono, Tulus; Sawitri, Hunik Sri Runing; Harsono, Mugi (LPPM IAIN Kudus, 2019)
The purpose of this study was to measure the effect of banking e-services quality on satisfaction of Islamic Saving and Credit Cooperatives. At present the banking sector is in a global business that prioritizes electronic services based on advances in information technology. The type of research methodology is field research and uses quantitative analysis based on primary data from 229 respondents total in Central Java Province. The results of testing the data using PLS Version 3.0, show that banking e-services quality has an effect on satisfaction of Islamic Saving and Credit Cooperatives. This is indicated by the magnitude of the e-services quality path coefficient on satisfaction and its significant is 0.461 to alpha 0.05, and t-value of the statistic is 7.754 * greater more than the t table is 1.65. this is indicates that e-services quality has a positive effect to satisfaction.